TARGET DAN SASARAN DALAM PENGEMBANGAN OBJEK WISATA KERATON AL-MUKARRAMMAH KABUPATEN SINTANG - Tri Wibowo E.01108114 (PublikA, Jurnal Ilmu Administrasi Negara, 2012)
ABSTRACTAim and objektive becomes a separate issue that affects the development of attraction. On the other side, the tourism attraction designed is closely with to the local communities. The Roles of Culture and Tourism as a related service that manages attraction, for a number of things, one internal party palace is still very protective in maintaining cultural assets attractions of Kraton AlMukarrammah. Activities undertaken palace often involve the wider community, the result will bethe development of knowledge societies attraction Kraton Al-Mukarrammah minimal. The influence of local budgets that focus on the natural attractions in Sintang resulting culturalattractions are also obstacles in the process of development, especially the private sector and nongovernmentalorganizationsKeywords: Aim and objektive, Development, Internal Party, Budget, and Privat